Evaluation of Serum Hepatocellular Enzymes in Nigerian with Goitre - Nnodim, Johnkennedy; Adamma, Emejulu; Ndubueze, Elendu Humphrey (Asian Journal of Medical Sciences, 2011)
Objective: The determination of serum gammaglutamyl transferase (GGT),alkaline phosphatase(ALP), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in patient with goitre in Owerri, Imo state Nigeria were investigated. Material & Methods: Thirty confirmed patients with goitre age 50 to 70years with the following thyroid index (Total T4 > 140.65±7.28nmol/l , Total T3 > 2.43±0.96nmol/l, Free T4 < 50.24±9.11nmol/l and TSH > 4.12±1.00nmol/l) were selected for the study. Thirty normal subjects free from goiter age 50 to 70 years were used as control. Patients with complications such as cardiovascular disease, hypertension and diabetes were excluded. Results: The level of serum gamaglutamyl transferase in goitre subjects was significantly higher (50.32 ±4.27 iu/l) when compared with control (17.50±3.94 iu/l) at P< 0.05. In the same vein the level of alkaline phosphatase was significantly higher (110.9m/l±12.92 iu/l) when compared with the control (56.3±12.06 iu/l) P<0.05. The levels of AST and ALT in goitre and control were not significant when compared with the control. Conclusion: This observation shows that gammaglutamyl transferase and alkaline phosphatase are frequently in-creased in goitre. Hence, they are possibly thyroid dependent enzymes. Key Words: Gammaglutamyl transferase; alkaline phosphatase; aspartateaminotransferase; alanine aminotransferase; thyroid hormones DOI: http://dx.doi.org/10.3126/ajms.v2i2.3870 Asian Journal of Medical Sciences 2 (2011) 79-81